Single-cell sequencing reveals the reproductive variations between primiparous and multiparous Hu ewes - Ting Ge; Yifan Wen; Bo Li; Xiaoyu Huang; Shaohua Jiang; Enping Zhang (Journal of Animal Science and Biotechnology, 2023)
Abstract Background In the modern sheep production systems, the reproductive performance of ewes determines the economic profitability of farming. Revealing the genetic mechanisms underlying differences in the litter size is important for the selection and breeding of highly prolific ewes. Hu sheep, a high-quality Chinese sheep breed, is known for its high fecundity and is often used as a model to study prolificacy traits. In the current study, animals were divided into two groups according to their delivery rates in three consecutive lambing seasons (namely, the high and low reproductive groups with ≥ 3 lambs and one lamb per season, n = 3, respectively). The ewes were slaughtered within 12 h of estrus, and unilateral ovarian tissues were collected and analyzed by 10× Genomics single-cell RNA sequencing. Results A total of 5 types of somatic cells were identified and corresponding expression profiles were mapped in the ovaries of each group. Noticeably, the differences in the ovary somatic cell expression profiles between the high and low reproductive groups were mainly clustered in the granulosa cells. Furthermore, four granulosa cell subtypes were identified. GeneSwitches analysis revealed that the abundance of JPH1 expression and the reduction of LOC101112291 expression could lead to different evolutionary directions of the granulosa cells. Additionally, the expression levels of FTH1 and FTL in mural granulosa cells of the highly reproductive group were significantly higher. These genes inhibit necroptosis and ferroptosis of mural granulosa cells, which helps prevent follicular atresia. Conclusions This study provides insights into the molecular mechanisms underlying the high fecundity of Hu sheep. The differences in gene expression profiles, particularly in the granulosa cells, suggest that these cells play a critical role in female prolificacy. The findings also highlight the importance of genes such as JPH1, LOC101112291, FTH1, and FTL in regulating granulosa cell function and follicular development.